(untitled) (International Journal of Innovative Technologies in Economy, 2018)
In this article practical aspects of using project management in popular restaurants of different countries are considered. Within the framework of this study, the experience of using the Hard Rock Cafe project management tools is highlighted. It is noted that the management of the project in Hard Rock Cafe includes three phases: planning, setting goals, defining the project and organizing the team; drawing up of a calendar schedule of works; control. Considered the project of opening a new restaurant from Pizza Duono (Italy). It stands out that in this restaurant project managers are in sight, they are responsible for: all necessary activities have been completed in the right sequence and on time; the project did not go beyond the budget; the project would meet the quality standards, etc. The study also examined an example of project caching to change the project completion time from the restaurant Pizza Duono (Italy, Rome). According to the methodology of this restaurant, on each of the critical paths the restaurant must identify one type of activity that can be subjected to crashing.